Implementasi Difusi Inovasi Pada Institut Pertambangan Nemangkawi di Papua Oleh PT Freeport Indonesia - Don Bosco Loho; Gitta Valencia (STARKI, 2017)
This research is done based on having an interest in development in developing countries by western assumption on diffusion innovation. The literature review, we could see how the Latin American countries being developed economically through capital-intensive industries. Surprisingly, it didn’t give any significant progress as the western researcher thought it would be. Meanwhile that happens, the urges of economic development in Papua, Indonesia has risen. Most Papuan has a low number of quality education this matters also to its human resources growth. As the biggest most influential corporation in Papua, PT Freeport Indonesia has given a chance to fulfill its act of corporate responsibility and the needs of Papuan society for human resources development through Nemangkawi Mining Institute. It is a training and education centre consist of innovative programs. As time goes by, critics emerge demanding the needs of a new alternative perspective for using diffusion of innovation in diverse nation. The research method used is qualitative, with personal interviews from corporate sources as well as participants of the Nemangkawi Mining Institute. Result of this research is a new explanation and understanding of the other side of PT Freeport Indonesia, which implemented through an innovative program at the Nemangkawi Mining Institute for the development of human resources in Papua that is self-reliant and qualified.Penelitian ini dilakukan dengan memperhatikan minat pembangunan di negara berkembang dengan asumsi barat terhadap difusi inovasi. Tinjauan literatur, kita melihat bagaimana negara-negara Amerika Latin dikembangkan secara ekonomi melalui industri padat modal. Anehnya, hal itu tidak memberikan kemajuan signifikan seperti yang diperkirakan oleh peneliti barat. Sementara itu yang terjadi, desakan pembangunan ekonomi di Papua, Indonesia telah meningkat. Kebanyakan orang Papua memiliki jumlah pendidikan yang rendah. Sebagai perusahaan terbesar yang paling berpengaruh di Papua, PT Freeport Indonesia telah memberikan kesempatan untuk memenuhi tanggung jawab perusahaan dan kebutuhan masyarakat Papua untuk pengembangan sumber daya manusia melalui Institut Pertambangan Nemangkawi. Ini adalah pusat pelatihan dan pendidikan yang terdiri dari program inovatif. Seiring berjalannya waktu, kritik muncul menuntut kebutuhan perspektif alternatif baru untuk menggunakan difusi inovasi di berbagai negara. Metode penelitian yang digunakan adalah kualitatif, dengan